Odpowiedzi

2010-03-12T17:14:50+01:00
A)-3(x-5)=2i1/2(8-4x)
-3x+15=5/2 (8-4x)
-3x+15=20-10x
-3x+10x=20-15
7x=5 /:7
x=5/7
b)0,5x-3i1/2=-4(7/8-0,125x)
0,5x- 7/2= -3,5-0,5x
0,5x+0,5x=-3,5+3,5
x=0
c)5(1,2x-1i1/4)=-9x+3i3/4
3x-6,5= -9x+3,75
3x+9x=3,75+6,5
12x=10,25 /:12
x=0,86 (ok.)
d)-4[-4(-4+3x)+3x]+3x=-(x+4)
-4[16-12x+3x]+3x=-x-4
64+48x+12x+3x=-x-4
63x+x=-4-64
64x=-68 /:64
x=-1,1 (ok.)
e)3x-2(4i1/2-4x)+1=x-2(1-5x)-6
3x-2(9/2-4x)+1=x-2+10x-6
3x-9+8x+1=x-2+10x-6
3x+8x-x-10x=-2+6+9-1
0=12
To równanie nie mam rozwiązania (równanie sprzeczne)
f)2x/7+3x/14+4x/21-x/42-0,5=x-2(1/4+x/6)
6x/21+6x/21+4x/21-x/42-0,5x=x-1/2+3x
16/21x-x/42-0,5x=x-1/2+3x
32/42x-x/42-0,5x=x-1/2+3x
31/42x-0,5x=x-1/2+3x /*42
31x-21x=42x-21+126x
10x-42x-126x=-21
-158x=-21 /:(-158)
x=0,13 (ok.)

Mam nadzieje,że pomogłam
Pozdrawiam!!!
9 2 9
2010-03-12T17:23:32+01:00
A)-3(x-5)=2i1/2(8-4x)
-3x+15=20-10x
-3x+10x=20-15
7x=5/:7
x=5/7

b)0,5x-3i1/2=-4(7/8-0,125x)
0,5x-3i1/2=-3,5+0,5x
0,5x-0,5x=-3,5+3,5
0=0

c)5(1,2x-1i1/4)=-9x+3i3/4
6x-6,25=-9x+3,75
6x+9x=3,75+6,25
15x=10/:15
x=2/3

d)-4[-4(-4+3x)+3x]+3x=-(x+4)
-4(16-12+3x)+3x=x-4
-64+48x-12x+3x=x-4
48x-12x+3x-x=-4+64
38x=60/:38
x=1i11/19

e)3x-2(4i1/2-4x)+1=x-2(1-5x)-6
3x-9+8x+1=x-2+10x-6
3x+8x-x-10x=-2-6+9-1
10x=0/:10
x=0
7 5 7